A Study of Written Noun Pattern Sequences among Secondary School Students in Malaysia - Sikder, Shafinaz; Nadzri, Nur Filzah Ahmad; Karunagaran, Laneesha (Journal of NELTA, 2021)
The following research work aimed to investigate the language change of learners through their usage of noun pattern in order to identify which words occur with which patterns and then create a repertoire of the three learners’ particular ways of using them. In order to do so, like previous studies, the study relied on the theoretical framework of Hunston’s Pattern Grammar Approach (1997) and the conceptual framework of Larsen-Freeman’s Complexity Theory (2006). This mixed method study adopted a longitudinal research approach into Chau (2015) students’ data to observe the commonly occurred noun pattern sequences within their writing tasks over three years. This helped to understand the changes on the noun pattern about language learning by associating meaning production via noun pattern sequences. Data collection and analysis method was adopted from Tashakkori & Teddlie, 2010. The codification of noun patterns were done quantitatively and then its frequency was quantified. The five nouns have been identified from the analysis at keyness cut-oﬀ of 25 via Keywords Extractor followed by a codification of noun pattern sequences done via the framework by Collins Cobuild English Dictionary and Francis et al. (1998). The result of the analysis shows that students do follow noun patterns yet they also tend to produce structures in their very unique ways. Likewise, the repetition of pattern over the years observed in learners suggests language could be both regressing and progressing simultaneously, unlike the developmental leader metaphor applied in most educational settings. In other words, the study suggests that students should be acquainted with patterns instead of words in isolation because their association with diﬀerent words makes them a natural accompaniment to a lexical approach. This paves the way for unorthodox scoring or marking system, shifting the focus from error analysis to meaningful production of language.